2018
DOI: 10.3390/ijerph15102147
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Purpose in Life, Grit, Gratitude, and School Belonging on Mental Distress among Chinese Emerging Adults

Abstract: Given the high prevalence of mental distress indicators, such as depression, among emerging adults, it is imperative to identify not only factors that place them at risk for mental distress, but also those that protect against it. This study tested the direct and indirect effects (via purpose in life) of gratitude, two aspects of grit (i.e., consistency of interest and perseverance of effort), and school belonging on three indicators of mental distress (i.e., depression, anxiety, and stress). A total of 468 Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 69 publications
3
40
0
5
Order By: Relevance
“…A recent study among university students in China revealed a negative relationship between one component of grit (consistency of interests) and depression, anxiety and stress. In the same study, however, it was found that perseverance of effort (another component of grit) was associated with depression but not with anxiety and stress [30]. Similarly, another recent study using path analysis found that grit was negatively associated with depression in a sample of high school students in the Philippines [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study among university students in China revealed a negative relationship between one component of grit (consistency of interests) and depression, anxiety and stress. In the same study, however, it was found that perseverance of effort (another component of grit) was associated with depression but not with anxiety and stress [30]. Similarly, another recent study using path analysis found that grit was negatively associated with depression in a sample of high school students in the Philippines [32].…”
Section: Discussionmentioning
confidence: 99%
“…Gritty people are likely to be less prone to adverse mental health outcomes, due to their propensity to experience obstacles and failures in a positive way. This relation between grit and mental health outcomes was demonstrated in three recent studies, which have all employed path analysis and have document a negative relationship between grit and mental health outcomes among university students in China [30], college students with a chronic medical condition in the United States [31], and high school students in the Philippines [32]. In the latter study [32], the authors found “meaning of life” to be a mediating factor of this association, and suggested that “gritty” people are likely to be less susceptible to depression, because they are more likely to realize that life is meaningful, and so they tend to focus on maintaining perseverance and passion to achieve their long-term goals, rather than on focusing on negative aspects of life [32].…”
Section: Introductionmentioning
confidence: 88%
“…Grit is conceptualized as passion and perseverance in the pursuit of long-term goals ( Duckworth et al, 2007 ; Duckworth, 2016 ). In recent years, many empirical studies have demonstrated the beneficial effects of grit on various psychological functions in individuals (see a meta-analysis by Credé et al, 2017 ), including young Chinese adults ( Zhang et al, 2018 ; Jin et al, 2019 ). Concerning the link between grit and depressive symptoms, Datu et al (2019) have found that it is negatively associated with depressive symptoms in their investigation of the presence of meaning in life among high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit limited, a burgeoning body of research has indicated that gritty individuals often exhibit better adaptive psychosocial functions, such as psychological wellbeing [ 33 , 34 , 35 ], prosocial behavior [ 28 ], personal relationships [ 10 ], and less mental distress [ 36 ]. Indeed, grit is a future-oriented motivation and might induce a sense of hope and determination, which further improves a sense of meaning in individuals’ lives and facilitates their positive interpersonal interactions.…”
Section: Introductionmentioning
confidence: 99%